1985
DOI: 10.1002/gepi.1370020107
|View full text |Cite
|
Sign up to set email alerts
|

Studies on vitiligo I. Epidemiological profile in Calcutta, India

Abstract: An epidemiological profile of vitiligo in Calcutta is presented. Prevalence data were gathered from 15,685 individuals drawn from the general population; pedigree data were collected through 293 vitiligo patients. The overall prevalence of vitiligo is about 5 per 1,000 individuals. There are no significant sex or age differences in prevalence rates. About a 4.5-fold increase in prevalence is observed among close biological relatives of affected individuals. There is, however, no clearcut correspondence between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
113
1
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 12 publications
10
113
1
3
Order By: Relevance
“…The present study shows that both males and females are vulnerable to the disease, a finding that is supported by other studies [2,11]. However, some investigators have recorded a higher incidence in women [1,3].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study shows that both males and females are vulnerable to the disease, a finding that is supported by other studies [2,11]. However, some investigators have recorded a higher incidence in women [1,3].…”
Section: Discussionsupporting
confidence: 91%
“…More than half of the patients in this study had the lesions in exposed areas of the body including face, head, neck, and extremities. The same finding was reported in other studies [10,11]. This will have its psychosocial effects and social stigma on patients with vitiligo, particularly in females.…”
Section: Discussionsupporting
confidence: 89%
“…7,8 In the present study, there were more women (58%) than men (42%). A similar finding has been noted in studies conducted in Brazil and China.…”
Section: Discussionsupporting
confidence: 40%
“…Men and women were affected equally. Another study from Calcutta, India showed prevalence of 0.5% with equal sex distribution 8 . However, another study done by Agrawal et al 9 found the prevalence of vitiligo to be 2.64%.…”
Section: Discussionmentioning
confidence: 97%